Comparative studies of essential oils from Matricaria recutita L. - O. I. Panasenko; V. M. Odyntsova; O. M. Denysenko; V. I. Mozul; V. V. Holovkin (Zaporozhye State Medical University, 2024)
The aim of the work is to determine the component composition of the essential oil of medicinal chamomile, grown on the educational and research site of medicinal plants of Zaporizhzhia State Medical and Pharmaceutical University (ZSMPHU), and commercial essential oil that was purchased via the Internet. Materials and methods. The object of the study was chamomile essential oil obtained by hydrodistillation and commercial oil. Qualitative and quantitative determination of the components of essential oils was established using the chromato-mass spectrometric method on a high-performance gas chromatograph "Agilent 7890B GC System" (Agilent, SantaClara, CA, USA) with a mass spectrometric detector "Agilent 5977 BGC/MSD" (Agilent, SantaClara, CA, USA). Results. Dominant compounds of essential oil of chamomile, grown on the educational and research site of medicinal plants ZSMPHU were 2H-pyran-3-ol, tetrahydro-2,2,6-trimethyl-6-(4-methyl-3-cyclohexen-1-yl) ) - 7.54 %, chamazulene - 5.32 %, alpha-bisabolol - 4.30 %, 1H-cycloprop[e]azulen-7-ol, decahydro-3,1,7-trimethyl-4-methylene - 3.25 %, myrtenyl acetate - 3.03 %, azulene, 1,2,3,3a,4,5,6,7-octahydro-1,4-dimethyl-7-(1-methylethenyl) - 2.16 %, bisabolol oxide B - 1.86 %. Commercial chamomile essential oil was dominated by 3-methoxy-3-methylbutanol (56.15 %), diethyl phthalate (17.46 %), linalyl acetate (6.99 %), linalool (4.41 %). Conclusions. Industrial cultivation of chamomile in southern Ukraine shows a high biologically active substances content and can be in demand in the pharmaceutical industry's consumer market for raw materials.